SPE Unconventional Resources Conference 2014
DOI: 10.2118/168984-ms
|View full text |Cite
|
Sign up to set email alerts
|

Imbibition Characteristics of the Barnett Shale Formation

Abstract: In order to understand the effect of injected stimulation fluids on nano-darcy permeability, naturally fractured shale reservoirs, an integrated study of spontaneous imbibition has been performed. In this study, oil recovery during spontaneous imbibition in naturally fractured shale samples was improved using different water formulations. Different water solutions were formulated by adding different amounts of HCl and NaOH to either distilled water or 2 wt% KCl-base brine solution. Eight water formulations, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 21 publications
1
17
0
2
Order By: Relevance
“…Several authors (Zhou et al 2014;Morsy and Sheng 2014;Makhanov et al 2014) have investigated the effect of fracturing fluid compositions on imbibition dynamics in shale. Zhou et al (2014) used shale samples from four different formations in the Horn River Basin in Canada and observed that the effect of fracturing fluid composition strongly depends on the clay content of shale rocks.…”
Section: Fluid Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors (Zhou et al 2014;Morsy and Sheng 2014;Makhanov et al 2014) have investigated the effect of fracturing fluid compositions on imbibition dynamics in shale. Zhou et al (2014) used shale samples from four different formations in the Horn River Basin in Canada and observed that the effect of fracturing fluid composition strongly depends on the clay content of shale rocks.…”
Section: Fluid Propertiesmentioning
confidence: 99%
“…They found that for shale with higher clay content, 2% KCl and 2% KCl substitute (two different fracturing fluids) imbibed 10% to 40% less than 0.07% friction reducer (as fracturing fluid); whereas, for shale with low clay content, 0.07% friction reducer is imbibed 10% to 30% less than 2% KCl, but no noticeable difference was found between 0.07% friction and 2% KCl substitute. Morsy and Sheng (2014) used shale samples from Barnett formation and reported two important observations: i) high pH solutions mixed with distilled water resulted in pore plugging due to combination of clay swelling and mineral dissolution, whereas high pH solutions mixed with higher alkaline concentrations (2 wt% NaOH) resulted in severely damaging the samples, ii) low pH solutions induced bedding cracks resulting in accelerating the imbibition. Makhanov et al (2014) used several shale samples from Horn River Basin in Canada and reported two main observations: i) use of xanthan gum results in significant imbibition despite its high viscosity, ii) anionic surfactants can reduce imbibition rates by reducing the surface tension, which is reduced further if the surfactant is mixed with KCl salt.…”
Section: Fluid Propertiesmentioning
confidence: 99%
“…x ¼ f 0 x r 0 z ¼ 19:5 MPa. The porosity of intact samples from the Barnett shale is measured with an average of 5.7% by Kale et al (2010), an average around 7% by (Morsy and Sheng 2014) and an average of 9.9% by Fu et al (2015). These porosity measurements cover a range from below 4% to more than 10%.…”
Section: A Case Study Of Barnett Shalementioning
confidence: 99%
“…Из за этого эксплуатация месторождения усложня ется. В связи с этим много работ было посвяще но изучению таких месторождении, в том числе и смачивающих свойств пород [Odusina, 2011;Wang, 2012;Shuler, 2011;Morsy, 2014;Alvarez, 2016]. Данные о смачиваемости породы позво лили правильно выбрать метод разработки этих месторождений.…”
Section: выдержанный участокunclassified